PACWIMA and the Transformation of Fijian Women in the Maritime Sector - Ningrum Surya Ningsi Pratiwi (Salasika, 2023)
The Pacific Women in Maritime Organization (PACWIMA) is a regional organization in the Pacific focused on empowering women to enhance their participation in the maritime sector. This regional organization serves as an international response to crucial issues such as gender inequality and sexual harassment, which contribute to the limited involvement of women in the maritime sector. Island nations like Fiji, heavily reliant on the maritime sector as a primary driver of national progress, also face these challenges. Through this research, we can gain insights into PACWIMA's role in addressing gender issues in Fiji's maritime sector and its contribution to promoting increased female participation. The study employs a qualitative research method with a case study framework and utilizes a feminist perspective, particularly liberal feminism, to analyze gender issues in this context. The findings indicate that PACWIMA can enhance women's roles in Fiji's maritime sector and mitigate gender-related problems within the industry. Beyond promoting gender equality in the maritime sector, PACWIMA also contributes to national economic stability by actively involving women as economic actors in the maritime sector.